Tolerance of foxtail, proso and pearl millets to saflufenacil - Reddy, Seshadri S.; Stahlman, Phillip W.; Geier, Patrick W.; Charvat, Leo D.; Wilson, Robert G.; Moechnig, Michael J. (My University, 2014)
Herbicide options for weed control in millets are very limited and hence there is a need for exploring potential herbicides. Field trials were conducted at three locations in Kansas and Nebraska in 2009 to evaluate foxtail millet, proso millet, and pearl millet tolerance to saflufenacil applied preemergence (PRE) at 36, 50, and 100 g aihaˉ¹. Foxtail millet was the most sensitive of the three millets to saflufenacil. Among experimental sites, saflufenacil at 36 g haˉ¹ injured foxtail millet 59 to 99% and reduced plant stands 41 to 95%; nearly all plants died at 100 g haˉ¹. Despite early season foliar injury and up to 36% stand reduction, fodder or grain yields of proso and pearl millets were not reduced by any rate of saflufenacil compared to untreated controls. Additional trials were conductedat four locations in Kansas, Nebraska and South Dakota in 2010 and 2011 to refine saflufenacil use rate (36 and 50 g haˉ¹) and application timing [14 days early preplant (EPP); 7 days preplant (PP); and PRE] for use in proso and pearl millets. Saflufenacil applied EPP or PP, regardless of rate, caused up to 21 and 6% foliar injury and up to 21 and 9% plant stand reduction in proso and pearl millets, respectively. However, yields were not reduced by EPP or PP treatments in either milletcrop. PRE applications of saflufenacil caused the highest crop injury and stand reduction in both millets. Saflufenacil PRE at 36 g haˉ¹ caused up to 57 and 40% foliar injury and up to 42 and 24% stand reductions in proso and pearl millets, respectively; however, yields were not affected. Comparatively, saflufenacil PRE at 50 g haˉ¹ reduced yields of proso and pearl millets 36 and 52%, respectively, on sandy loam soilswith high pH (8.3) and low organic matter content (1.1%).Overall, results indicated that foxtail millet lacks tolerance to saflufenacil, but up to 50 g haˉ¹ of saflufenacil maybe safely applied as near as 7 days before planting proso or pearl millets. If situation demands, saflufenacil at 36 g haˉ¹ can also be applied PRE to either crop with risk of some crop injury.
Keywords: Crop injury; Herbicide; Millets; Preemergence; Preplant; Saflufenacil; Weed management